Effect of untreated effluent on histopathological constituents of fresh water fish, tilapia Oreochromis mossambicus - M.VIJAYALAKSHMI,; T.SHEHNAZ BEGUM, (International Journal of Pharma and Bio Sciences, 2017)
The physicochemical parameters (pH,BOD, COD, TDS, TSS, total chromium and Hexavalent chromium) of untreated tannery effluent and its effects on the histoptathological constituents present in gills, liver and muscle of tilapia were studied. The results of analysis of physico chemical parameters of untreated tannery effluent revealed that the parameters were found to be higher than the permissible limits of CPCB(1995) thereby indicating the high pollution potential of the tannery effluent. LC50 analysis was conducted for different lengths of time of at various concentrations. Histopathological observations were made on gills, muscle and liver tissues of tilapia fish at two intervals of 15 and 30 days. The gills of fish exposed to untreated tannery effluent for 30 days resulted in histopathological changes such as fusion and shortening of secondary lamellae and epithelial necrosis. In liver, it showed severe disorganization of hepatic cells, damaged cell membrane, necrosis, sinusoids were observed. Likewise, In muscle, there was vacuolar degeneration of muscle bundle with aggregation of inflammatory cells, atrophy of muscle bundles and splitting of muscle fibres.